1981
DOI: 10.1093/jac/8.suppl_b.263
|View full text |Cite
|
Sign up to set email alerts
|

The comparative pharmacokinetics of ceftazidime and cefotaxime in healthy volunteers

Abstract: The pharmacokinetic behaviour of two aminothiazolyl cephalosporins, ceftazidime (CAZ) and cefotaxime (CTX), were compared in three studies. Doses of each antibiotic were given intravenously (500 mg, n=4; 1 g, n=4) or intramuscularly (1 g, n=8) in a cross-over manner to healthy male volunteers. Antibiotic assays were performed by HPLC and microbiological assay techniques. Both antibiotics appeared to fit a two-compartment iv kinetic model with terminal half-lives of 1.7 h (CAZ) and 0.8 h (CTX). CAZ was metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
1
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 0 publications
3
30
1
1
Order By: Relevance
“…The in vitro properties of ceftazidime against these four strains were first described by Wise et al (52). Our results were in the same range and were also reported by others (7,18,19,21,49). SCE-2787 showed a minimal bactericidal concentration against P. aeruginosa after 440 min following the end of infusion, while ceftazidime showed it after 360 min.…”
Section: Discussionsupporting
confidence: 90%
“…The in vitro properties of ceftazidime against these four strains were first described by Wise et al (52). Our results were in the same range and were also reported by others (7,18,19,21,49). SCE-2787 showed a minimal bactericidal concentration against P. aeruginosa after 440 min following the end of infusion, while ceftazidime showed it after 360 min.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the results of previous studies showing ratios of between 0.65 and 0.97 (2). The combination of a ceftazidime/inulin clearance ratio of 0.72 and the previously reported low (17%) protein binding suggests that renal elimination of ceftazidime is almost completely mediated by glomerular filtration (10). A recent study with adults indicated that in addi- tion to glomerular filtration, some tubular excretion of ceftazidime, which is probably triggered by passive reabsorption, occurs (24).…”
Section: Discussionsupporting
confidence: 93%
“…samples stored at -20°C. Ceftazidime was also stable in urine for 2 weeks at -20°C; however, in serum, especially at the lower concentrations, there was a small loss (<10%) of activity after 1 week, increasing to 22% after 2 weeks, and 73% after 4 weeks. Therefore, ceftazidime samples were assayed within 48 h, and moxalactam samples were assayed within 1 week.…”
mentioning
confidence: 91%